Positive expressive writing interventions, subjective health and wellbeing in non-clinical populations: A systematic review - Lauren M. Hoult; Mark A. Wetherell; Trudi Edginton; Michael A. Smith (PLoS ONE, 2025)
Positive expressive writing has been increasingly researched over the past two decades due to its potential to serve as a low-intensity psychological self-help intervention. However, studies are heterogeneous in their methodologies and the health and wellbeing outcomes targeted, and it is unclear which outcomes are most reliably benefited by positive writing techniques. This systematic review aimed to determine the optimal conditions under which positive expressive writing interventions benefit subjective health and wellbeing in non-clinical populations. A systematic search was conducted across four databases (Web of Science, Scopus, PubMed, and ProQuest: APA PsychArticles) identifying peer-reviewed articles written in the English language from 1930 to August 2023. A total of 51 studies were identified and included seven different positive writing techniques: best possible self, positive experiences, gratitude, benefit finding, satisfaction processes, three good things and resource diary. Most consistent benefits were found for wellbeing and positive affect outcomes (e.g., optimism, happiness) whereas less consistent effects were reported for negative affect, psychological health (e.g., stress, anxiety) and physical health outcomes. Best possible self and gratitude interventions revealed most consistent benefits. Several moderators were identified indicating that benefits may depend on individual differences relating to wellbeing, emotional and social factors. While reasonably consistent benefits of positive expressive writing were observed for wellbeing outcomes, the quality of all studies included in the review was assessed to be poor or fair. Thus, it is clear that more rigorous methods, including intention-to-treat analyses and robust reporting of methods and findings are needed. Future work should also aim to replicate the moderation effects reported in the present review, to enable a better understanding of the individual differences which influence the efficacy of positive expressive writing effects.